A reconfigured Kennedy pathway which promotes efficient accumulation of medium‐chain fatty acids in leaf oils. Issue 11 (3rd May 2017) - Reynolds, Kyle B.; Taylor, Matthew C.; Cullerne, Darren P.; Blanchard, Christopher L.; Wood, Craig C.; Singh, Surinder P.; Petrie, James R.
Summary: Medium‐chain fatty acids (MCFA, C6‐14 fatty acids) are an ideal feedstock for biodiesel and broader oleochemicals. In recent decades, several studies have used transgenic engineering to produce MCFA in seeds oils, although these modifications result in unbalance membrane lipid profiles that impair oil yields and agronomic performance. Given the ability to engineer nonseed organs to produce oils, we have previously demonstrated that MCFA profiles can be produced in leaves, but this also results in unbalanced membrane lipid profiles and undesirable chlorosis and cell death. Here we demonstrate that the introduction of a diacylglycerol acyltransferase from oil palm, EgDGAT1, was necessary to channel nascent MCFA directly into leaf oils and therefore bypassing MCFA residing in membrane lipids. This pathway resulted in increased flux towards MCFA rich leaf oils, reduced MCFA in leaf membrane lipids and, crucially, the alleviation of chlorosis. Deep sequencing of African oil palm ( Elaeis guineensis ) and coconut palm ( Cocos nucifera ) generated candidate genes of interest, which were then tested for their ability to improve oil accumulation. Thioesterases were explored for the production of lauric acid (C12:0) and myristic (C14:0). The thioesterases from Umbellularia californica and Cinnamomum camphora produced a total of 52% C12:0 and 40% C14:0, respectively, in transient leaf assays. This study demonstrated that the introduction of a complete acyl‐CoA‐dependent pathway for the synthesis of MFCA‐rich oils avoided disturbing membrane homoeostasis and cell death phenotypes. This study outlines a transgenic strategy for the engineering of biomass crops with high levels of MCFA rich leaf oils.